2009
DOI: 10.5536/kjps.2009.36.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Oligosaccharides on the Performance, Intestinal Microflora and Serum Immunoglobulin Contents in Laying Hens

Abstract: This study was conducted to investigate the effects of dietary supplementation of mannan-oligosaccharides (MOS) and fructo-oligosaccharides (FOS) on the performance, immune response and small intestinal microflora in laying hens. A total of 960 Hy-Line Brown Ⓡ laying hens of 27 wks old, housed in 2 bird cages, were assigned in a completely randomized block design into one of the following 6 dietary treatments: control, antibiotic (6 ppm avilamycine), 0.025% MOS, 0.05% MOS, 0.25% FOS, and 0.5% FOS. Each treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In other studies, however, IgA was increased in laying hens (Kim et al, 2009) ed that IgG levels were increased by MOS supplementation in turkeys, and Woo et al (2007) reported that IgG was increased by MOS supplementation in layers. Yin et al (2008) reported that supplementation with a prebiotic oligosaccharide galacto-mannan increased the serum levels of IgA, IgG, and IgM compared with the level of lincomycin in early-weaned pigs.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In other studies, however, IgA was increased in laying hens (Kim et al, 2009) ed that IgG levels were increased by MOS supplementation in turkeys, and Woo et al (2007) reported that IgG was increased by MOS supplementation in layers. Yin et al (2008) reported that supplementation with a prebiotic oligosaccharide galacto-mannan increased the serum levels of IgA, IgG, and IgM compared with the level of lincomycin in early-weaned pigs.…”
Section: Resultsmentioning
confidence: 92%
“…Mikkelsen et al (2004) reported that a high level of FOS increases gas production by intestinal microbiota, which causes diarrhea. Dietary mannan oligosaccharides improved broiler and turkey performance at a level of 0.0125 to 0.1% (Hooge, 2003;Sims et al, 2004) and improved the egg production of layers at a level of 0.025 to 0.05% (Woo et al, 2007;Kim et al, 2009).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The ability of MOS to mature dendritic cells was shown to be mediated through a TLR4‐dependent mechanism (Sheng et al., ). It is also reported that supplementation of MOS increased the synthesis of Ig, particularly IgA (Kim et al., ). In this context, Avinew ND vaccine combined with AH and/or MOS adjuvants was used to vaccinate embryos of commercial pullets in our study to examine the efficacy of these types of vaccinations.…”
Section: Discussionmentioning
confidence: 93%
“…The decrease in pathogens and increase in beneficial bacteria may be because of competition for receptor sites, and the production of volatile fatty acids, of some bacteriocins, and of IgA antibodies by the immune system of the host (Brzoska et al, 2007;Kim et al, 2009). Owing to these beneficial changes in microflora, the number of goblet cells and length of intestinal villi increase, which ultimately promotes the health and functions of the GIT of the host (Rehman et al, 2009;Bonos et al, 2010;Vahdatpour et al, 2011).…”
Section: Introductionmentioning
confidence: 99%